2021
DOI: 10.1136/bmjophth-2020-000611
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser trabeculoplasty (SLT) performed by optometrists for patients with glaucoma and ocular hypertension: a scoping review

Abstract: Selective laser trabeculoplasty (SLT) has been established as an effective treatment to lower intraocular pressure in people with glaucoma and ocular hypertension. The procedure is typically within the remit of ophthalmologists; however, there is potential to upskill optometrists and other healthcare professionals (HCPs) to deliver the treatment. We conducted a scoping review to identify the current global landscape of HCP-delivered SLT and describe training features, clinical effectiveness and safety. Relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Clinicians expected the training to maintain the existing apprenticeship format [ 4 , 5 ]; optometrists would undergo theoretical clinical and laser safety training, followed by a period of observing, delivering SLT under supervision and then being signed off as competent. Chadwick et al [ 4 ] reported a minimum of five supervised procedures, similar to the Moorfields protocol for non-medical SLT training [ 24 ], but this was often exceeded, mainly due to a lack of adequate challenging cases or self-confidence [ 4 ]. In agreement with the literature, clinicians interviewed for this study identified that practical training should follow a skills based approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians expected the training to maintain the existing apprenticeship format [ 4 , 5 ]; optometrists would undergo theoretical clinical and laser safety training, followed by a period of observing, delivering SLT under supervision and then being signed off as competent. Chadwick et al [ 4 ] reported a minimum of five supervised procedures, similar to the Moorfields protocol for non-medical SLT training [ 24 ], but this was often exceeded, mainly due to a lack of adequate challenging cases or self-confidence [ 4 ]. In agreement with the literature, clinicians interviewed for this study identified that practical training should follow a skills based approach.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the literature, clinicians interviewed for this study identified that practical training should follow a skills based approach. The current lack of training standardisation [ 3 , 4 , 24 ] may be linked to difficulties in ensuring an adequate case mix and the subsequent delay in clinical readiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 , 19 This assertion is corroborated by a study in the UK, which found that optometrists trained in glaucoma management could potentially manage and treat patients with ocular hypertension in the community without a referral to an ophthalmologist. 20 , 21 Moreover, specially trained and accredited optometrists working independently within the hospital environment, monitoring glaucoma and glaucoma-suspected patients were seen to be capable of making clinical management decisions that were in close agreement with those of glaucoma-specialist consultant ophthalmologists. 20 Considering that patients with conditions such as ocular hypertension and glaucoma require lifelong management usually by an ophthalmologist, and often within an institution in the public sector, the comparatively lower numbers of ophthalmologists to optometrists worldwide serve as an impediment to the availability of safe, prompt and effective treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Optometrists provide significant capacity within glaucoma pathways, involving detection, diagnosis, monitoring and treatment [ 23 , 24 ]. Despite these contributions, there has been little qualitative research on whether care by optometrists is an accepted alternative to traditional-care, and what factors impact development and sustainability of glaucoma services with optometric involvement.…”
Section: Discussionmentioning
confidence: 99%